Researching and Transforming Adult Learning and Communities: The Local/Global Context (Research on the Education and Learning of Adults, 2016)
The chapters of this volume reflect ongoing research in the field of adult education and learning in and with communities. At the same time the work of the authors presented here offers a very vital reflection of the work of the ESREA research network Between Local and Global-Adult Learning and Communities. The chapters showcase the broad range of professional practice, the variety in both methodology and theoretical background, as well as the impressive scope of field research experience the authors bring to bear in their papers. Readership: Educational Researchers and their students